What can be learned from China's success?*. Issue 1 (2nd January 2016) - Ross, John; Zheng, Jinghai; Prime, Karla Simone
Abstract : Since 1978, China has experienced the most rapid economic growth of any country in world history, and the most rapid growth in living standards of any major economy. Following the latest international financial crisis, China outperformed any other major economy – from the second quarter of 2007 to the second quarter of 2014, China's economy grew by 78% and the USA by 8%. In a single generation, China has gone from a 'low income economy' to the verge of achieving 'high income' status by World Bank criteria. Achieving this would double the population living in 'high income' economies globally. This extremely rapid development is sometimes explained in terms of unique 'Chinese characteristics', but research over the last 30 years suggests it is rooted in universal economic processes. While the combination of global forces producing economic growth is unique in China and produces unique 'Chinese characteristics', they can operate throughout the world economy. If other developing economies could achieve the scale of China's economic success, global problems of poverty and its consequences would be solved. China's policy response to the international financial crisis was far more effective than that of other major economies. This paper examines the chief strategic lessons to be drawn from China's success.